Oriented Antibody Covalent Immobilization for Label-Free Impedimetric Detection of C-Reactive Protein via Direct and Sandwich Immunoassays - Adesina, Abiola; Mashazi, Philani (Frontiers in Chemistry, 2021)
The detection and monitoring of biological markers as disease indicators in a simple manner is a subject of international interest. In this work, we report two simple and sensitive label-free impedimetric immunoassays for the detection of C-reactive protein (CRP). The gold electrode modified with boronic acid terminated self-assembled monolayers afforded oriented immobilization of capture glycosylated antibody (anti-human CRP monoclonal antibody, mAb). This antibody modified surface was able to capture human CRP protein and the impedance signal showed linear dependence with CRP concentration. We confirmed the immobilization of anti-CRP mAb using surface sensitive X-ray photoelectron spectroscopy (XPS) and electrochemical impedance. The oriented covalent immobilization of mAb was achieved using glycosylated Fc (fragment, crystallisable) region specific to boronic acid. The direct immunoassay exhibited a linear curve for concentrations range up to 100 ng.mL-1. The limit of detection (LoD) of 2.9 ng.mL-1, limit of quantification (LoQ) of 9.66 ng.mL-1 and sensitivity of 0.585 kΩ.ng-1.mL.cm-2 were obtained. The sandwich immunoassay was carried out by capturing polyclonal anti-CRP antibody (pAb) onto the CRP-antigen immunoreaction. The impedance signal after pAb capture also showed linear dependent with CRP antigen concentration and acted as a CRP antigen detection signal amplifier. The detection of the CRP antigen using sandwich pAb immunoassay improved LoD to 1.2 ng.mL-1, LoQ to 3.97 ng.mL-1 and enhanced the sensitivity was 0.885 kΩ.ng-1.mL.cm-2. The real sample analysis, using new born calf serum, showed excellent selectivity and % recovery for the human CRP ranging from 91.2 to 96.5%. The method was reproducible to 4.5% for direct immunoassay and 2.3% for sandwich immunoassay.